Elderly Gravida with Bombay Blood Group and Placenta Previa Managed with Autologous Blood Transfusion - Pooja Paudyal; Geeta Gurung; Ashmita Adhikari; Suvana Maskey; Josie Baral (Case Reports in Obstetrics and Gynecology)
The Bombay blood group is a rare blood type with an incidence of around one in a million. There is no known reported case of an obstetric patient with the Bombay blood group from Nepal. People with this rare blood group can receive blood only from those with the same blood type. We report an elderly gravida with the Bombay blood group who had a pregnancy complicated by diabetes, placenta previa, and transverse lie (back up) following an in vitro fertilization. Placenta previa posed a greater risk of hemorrhage and hence the need for transfusion. The main challenge was arranging blood for transfusion, and as the Bombay blood group was unavailable, she was managed with autologous blood transfusion which was performed for the first time in a pregnant lady in our institute. She underwent Cesarean section for placenta previa with transverse lie, and both mother and baby were sent home in good health.